Social Categorization and Stereotyping as the Structural Procedural Components of Social Cognition - Ivanyuk, N. M. (Psychological Prospects Journal, 2011)
The article outlines the interdisciplinary theoretical principles of complex research of the concept of Cognition. The emphasis is on social categorization and stereotyping as important psychological procedural components of Social Cognition.